The critical reception of Hemingway's The sun also rises - Hays, Peter L., 1938- (Studies in American literature and culture. Literary criticism in perspective., 2011)
"In the eight decades since its publication, Hemingway's The Sun Also Rises, like a Rorschach blot, has measured not only critics' opinions of Hemingway but also the critical temper of the times. An initial reviewer saw the book as a satire on American expatriates, an unflattering portrait of wastrels and a nymphomaniac wandering Europe. Other critics of the time saw it as a reflection of post-First World War malaise, inscribing for history the Lost Generation -- those critics, that is, who took it as a serious literary effort and did not simply dismiss it as pornographic, as Hemingway's own parents did. Since then the novel has been interpreted, variously, as a study of an impotent man's existential dilemma, re-read as a modern-day version of the Fisher King myth, attacked by feminist critics as the macho diatribe of a misogynist, and, most recently, seen as a study of gender roles and the performance of masculinity. There is no other book that surveys the entire span of The Sun Also Rises criticism, documents the fashionable waves in which criticism has traveled, and points out how each age interprets the novel to suit itself, reflecting the cultural concerns of the moment"--Provided by publisher.